Made for Mughal emperors royal treasures from Hindustan - Stronge, Susan (I. B. Tauris, 2010)
Susan Stronge's lavishly illustrated new book tells the stories behind the artwork, revealing the lives and livelihoods of those who redefined the world of Islamic art. She traces the route from the craftsmen in the workshops to the royalty and nobles who commissioned the exquisite pieces